ANALISIS PENGEMBANGAN SISTEM ANTRIAN ONLINE BERBASIS WEB UNTUK MENINGKATKAN EFISIENSI PELAYANAN DENGAN WEBTREE PADA KLINIK KECANTIKAN - Nathalia Margaretha; Jenny Christine; Dorie P. Kesuma (CV. Denasya Smart Publisher, 2026)
The development of information technology has a significant impact on the improvement of service quality the quality of services in various fields, including health and beauty service. Beauty clinics, as one of the service facilities that continue to develop, require an effective and efficient service system to address queue problems that are still managed manually. Manual queuing systems result in long waiting times, disorderly queue management, and the accumulation of customers in the waiting room. This study aims to analyze the development of a web-based online queuing system with the application of a web tree structure to improve service efficiency at beauty clinics. The research method used is qualitative research with a literature study approach through data collection from scientific journals, books, and articles related to developing technology, online queuing systems, websites, and web trees. Research results show that a web-based online queue system is able to improve service efficiency, provide real-time queue information, reduce waiting room congestion, and increase customer satisfaction. The implementation of a web tree also helps in organizing the system's navigation structure to be more organized and easy to use. Thus, a web-based online queue system supported by a web tree becomes an effective emerging developing technological solution in improving service quality at beauty clinics.